2017
DOI: 10.1093/gerona/glw242
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal Proteolysis Is Associated With Exercise-Induced Improvement of Mitochondrial Quality Control in Aged Hippocampus

Abstract: Exercise improves cognitive function in older adults, but the underlying mechanism is largely unknown. Both lysosomal degradation and mitochondrial quality control decline with age. We hypothesized that exercise ameliorates age-related cognitive decline through the improvement of mitochondrial quality control in aged hippocampus, and this effect is associated with lysosomal proteolysis. Sixteen to eighteen-month old male Sprague Dawley rats underwent swim exercise training for 10 weeks. The exercise regimen pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 54 publications
2
17
0
1
Order By: Relevance
“…Similar beneficial effects of regular exercise have been reported for young and old mice with ablation of PGC-1α, when hyper-fragmentation of mitochondrial networks was observed in aged relative to young animals, and exercise training normalized mitochondrial network structure in wild, but not in PGC-1α KO animals [50] or in human subjects [51]. The beneficial effects of exercise on mitochondrial dynamics is not limited to skeletal muscle, but also includes brains [29,52,53] and fetal hearts from exercised dams [54], while other organs have not been studied.…”
Section: Mitochondrial Dynamics In Exercise and Agingsupporting
confidence: 62%
“…Similar beneficial effects of regular exercise have been reported for young and old mice with ablation of PGC-1α, when hyper-fragmentation of mitochondrial networks was observed in aged relative to young animals, and exercise training normalized mitochondrial network structure in wild, but not in PGC-1α KO animals [50] or in human subjects [51]. The beneficial effects of exercise on mitochondrial dynamics is not limited to skeletal muscle, but also includes brains [29,52,53] and fetal hearts from exercised dams [54], while other organs have not been studied.…”
Section: Mitochondrial Dynamics In Exercise and Agingsupporting
confidence: 62%
“…Mitochondrial quality control consists of a series of mechanisms, including reactive oxygen species (ROS) scavenging, mitochondrial dynamics, and mitophagy. Studies have revealed that exercise improves mitochondrial quality both in healthy [ 10 ] and in metabolic and neurodegenerative disorders as well as in aging [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…When cells are exposed to long-term nutrient deprivation and energy loss, an excess amount of lipolysis results in the production of ketone bodies, which are the end product of free fatty acid oxidation reaction and can be used as an energy source in muscle and neurons. Since not all cells have the ability to use ketone bodies as an energy source, the cells that cannot utilize these small molecules activate proteolysis as a response to starvation (Luo et al 2017;Lee et al 2017). Proteolysis can be activated in two different ways, depending on the tissue type and stress duration.…”
Section: Introductionmentioning
confidence: 99%